Positive attitudinal shifts and a narrowing gender gap: Do expertlike attitudes correlate to higher learning gains for women in the physics classroom? - Alma Robinson (American Physical Society, 2021)
A large body of research shows that using interactive engagement pedagogy in the introductory physics classroom consistently results in significant student learning gains; however, with a few exceptions, those learning gains tend not to be accompanied by more expertlike attitudes and beliefs about physics and learning physics. In fact, in both traditionally taught and active learning classroom environments, students often become more novicelike in their attitudes and beliefs following a semester of instruction. Furthermore, prior to instruction, men typically score higher than women on conceptual inventories, such as the Force Concept Inventory (FCI), and more expertlike on attitudinal surveys, such as the Colorado Learning Attitudes about Science Survey (CLASS), and those gender gaps generally persist following instruction. In this paper, we analyze three years of pre-post matched data for physics majors at Virginia Tech on the FCI and the CLASS. The courses were taught using a blended pedagogical model of peer instruction, group problem solving, and direct instruction, along with an explicit focus on the importance of conceptual understanding and a growth mindset. We found that the FCI gender gap decreased, and both men and women showed positive, expertlike shifts on the CLASS. Perhaps most surprisingly, we found a meaningful correlation between a student’s post-CLASS score and normalized FCI gain for women, but not for men.